Of Books and their Covers: Marketing Fiction in a Globalized Context - Mandal, Somdatta (EAST WEST JOURNAL OF HUMANITIES, 2011)
Though a book is not supposed to be judged by it cover, the truth is publishers do their best to make us do so. This paper looks at different strategies deployed by leading publishers to market books and their authors through carefully thought out covers and blurbs. It follows the history of the publication of some key novels by South Asian writers, namely Arundhoti Roy. Salman Rushdie and Jhumpa Lahiri, to show how their works have been designed for niche markets. In fact, it demonstrates how the same book is provided with different covers for different markets and different historical moments to capture particular groups of the reading public. This paper concludes that publishers pursue a policy of blending the global and the local too since their priority is the selling of the books and not merely intellectual stimulation.